2018
DOI: 10.1159/000490626
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Intervention for Primary Caries Lesions: Are Dentists Implementing This Concept?

Abstract: Contemporary minimally invasive treatment concepts for restorative treatment of primary caries lesions include both delayed intervention and smaller-sized preparations restricted to removal of carious tissue. The aim of this study was to investigate whether these concepts have resulted in a trend towards a more conservative choice made by dentists regarding treatment thresholds and restorative techniques. The results from previously conducted, precoded questionnaires developed by Espelid and Tveit, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 38 publications
(44 reference statements)
2
37
1
8
Order By: Relevance
“…6.7 Recently, a web-based questionnaire survey was conducted in Scandinavia to determine the trend of using MID. 8 The study has shown that dentists from countries with a high socioeconomic level still tend to intervene operatively at a very early stage of caries, although there are variations among the countries evaluated. However, there is no information on this trend in developing countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 98%
“…6.7 Recently, a web-based questionnaire survey was conducted in Scandinavia to determine the trend of using MID. 8 The study has shown that dentists from countries with a high socioeconomic level still tend to intervene operatively at a very early stage of caries, although there are variations among the countries evaluated. However, there is no information on this trend in developing countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 98%
“…Aggravating the problem, using rotary burs, and cutting instruments in the conventional invasive treatment of proximal lesions sacrifice substantial amounts of sound tooth structure. This violates the concept of minimally invasive dentistry (MID)[45] which involves excavating the least possible amount of dental tissues. [6] Consequently, resin infiltration was invented.…”
Section: Introductionmentioning
confidence: 99%
“…The internationally accepted "gold standard threshold" for minimally invasive operative interventions currently refers to proximal lesions radiographically extending beyond the outer third of dentin (with recommendations aiming at predominantly saucer-shaped preparations as the favored cavity design) [68]. This mainly is owed to the fact of increasing cavitation probabilities of the outer enamel surface [33,34,69], and these breakdowns, in turn, correspond to impaired biofilm removal and decreasing remineralization capabilities (even with patients showing normal salivary function [70]); moreover, it is well-known that lesions extending clearly beyond the enamel-dentin border (> 0.5 mm) are most likely to progress within a period of 3 years [71], and comparable deteriorations have been reported with increasing ICDAS severities [36].…”
Section: Discussionmentioning
confidence: 99%